The Geometric Design of Horizontal Alignment: A Case Of Post-Harvest Infrastructure Corn Drying Center, Tuban, East Java - Litwina Ratri Rosaria; Andri Irfan Rifai; Joewono Prasetijo (International Journal Labs, 2022)
One of the aspects put forward in modern times is road infrastructure to meet the needs of moving goods, services, and people. As well as road planning for toll roads, connecting roads between regions, and roads in specific areas such as industrial areas, it also requires careful planning to meet the needs of transportation movement in them. This analysis focuses on the geometric road planning for horizontal paragraphs in the Corn Drying Center Post-Harvest Infrastructure industrial area in Tuban, East Java. The planning considers daily vehicle flows, heaviest axis loads, and bend radiuses that adjust for a limited land area. Correspondence to data in the field is obtained from the results of surveys that have been conducted (quantitative data). The result of the calculations is depicted using AutoCAD Civil 2D®.